Unraveling the multifaceted roles of extracellular vesicles in bladder cancer: diagnostic insights and therapeutic opportunities - Huang, Kaiqi; Yang, Chen; Xu, Yanfang; Wang, Yujia (Frontiers in Oncology, 2025)
Bladder cancer, predominantly urothelial carcinoma, is a global health issue with increasing incidences and mortality. It poses significant diagnostic and therapeutic challenges due to its molecular heterogeneity and the limitations of current detection methods. Extracellular vesicles (EVs), including exosomes, play a crucial role in intercellular communication and have emerged as potential biomarkers and therapeutic agents in bladder cancer. This review focuses on the multifaceted roles of EVs in bladder cancer biology, their potential as diagnostic biomarkers, and their use in therapeutic strategies. We discuss how EVs reflect molecular subtypes of bladder cancer, participate in metabolic reprogramming and angiogenesis, and modulate cellular behavior. The review also highlights the advances in proteomic analysis of urinary and tissue-exudative EVs, identifying specific proteins and RNAs that could serve as non-invasive diagnostic markers. Furthermore, we explore the innovative use of EVs as natural nanocarriers for drug delivery in bladder cancer treatment, demonstrating their potential to enhance the efficacy of chemotherapy and selectively target cancer cells. The integration of EV-based diagnostics with traditional methods could lead to more personalized and effective bladder cancer management, emphasizing the need for further research and clinical validation.